Transformasi Digital Dalam Praktik Kenotariatan: Implementasi Sertifikat Elektronik Untuk Akta Otentik Berdasarkan Undang-Undang Jabatan Notaris - Maulita Tri Rosyida; Rusdianto Sesung; Habib Adjie (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
Digital transformation has rapidly penetrated various sectors, notably including notarial practices across Indonesia. This article is dedicated to analyzing the practical implementation of electronic certificates when notaries manufacture authentic deeds. The analysis refers specifically to Law No. 2 of 2014, which amends the Notary Position Law (UUJN), and examines its relationship with the Law on Information and Electronic Transactions (UU ITE). The adoption of electronic certificates and electronic signatures (TTE) holds significant promise, aiming for efficiency, speed, and enhanced security of legal documents, fully aligning with the modern concept of